Older adult sexuality in the practice and training of geriatricians: a qualitative study - Bruna Almeida Andrade Velloso; Ana Carolina Toscano Coelho Bezerra Costa; Carolina Ferreira Farias; Rayanne Victória Araújo Lins Rocha; Cesar Romero do Nascimento Lyra Filho; Arturo de Pádua Walfrido Jordán; Leopoldo Nelson Fernandes Barbosa (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To understand the academic training of geriatrics residents and their supervisors regarding the sexuality of older adults, as well as practical approaches to the subject in their work routines. METHODS: This qualitative study was conducted with geriatrics residents and their supervisors at a public hospital in Recife, PE, Brazil in 2019 and 2020. RESULTS: A partial understanding of the respondents' concept of sexuality was identified through statements that expressed confusion between sexual intercourse and sexuality, as well as a lack of knowledge about sexuality on an individual level. Although the respondents affirmed the importance of discussing the subject, they reported that they do not, except passively. The respondents discuss this issue depending on the patient's questions, despite acknowledging their difficulty in seeking a health service to talk about sexuality-related issues. Finally, the lack of an approach to sexuality in geriatric consultations was linked with gaps in undergraduate and specialization programs about general care for older adults, resulting in a feeling of unpreparedness to face the taboos and prejudices associated with sexuality. CONCLUSION: Although professionals consider it important to address sexuality with patients, most of them do not do so in medical consultations due to a number of difficulties, including the lack of a protocol to follow, which leads to a passive approach. Therefore, professionals acknowledge the difficulty of addressing the subject and associate it with deficiencies in their academic training.